What Kinds of Research Information Do Communications Practitioners Need? - John Pates (Journal of Applied Communications, 1987)
Listen to a communicator attending any conference related to their work and one could conclude that the mission of the average communications office has become: "Do more, do it better, do it with LESS!! Not only on less money...but less time!" Now, if that isn't the perfect recipe for frustration, it would be hard to find one. Unfortunately, it seems to be a feeling shared by many.